2020
DOI: 10.4081/ija.2020.1418
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of NDVI index to pea condition evaluation at diverse phosphorus fertilization

Abstract: In this 3-year study the suitability of the normalized differenced vegetation index (NDVI) to the evaluation of pea plant infestation by aphids and expected seeds yield was investigated. The effect was assessed in the conditions of the increasing doses of phosphorus fertilization (0, 70, and 140 kg P2O5 ha–1) and in the different pea aphid (Acyrthosiphon pisum Harris) occurrence on six various cultivars of pea. Independent of the dose, the phosphorus fertilization supported the occurrence of aphids on pea plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Easily available forms of phosphorus contained in the applied foliar fertiliser produced a positive effect on the nutritional status of maize in the experimental variants F1 and F3, which was confirmed by the values of NDVI. A relationship between phosphorus and leaf greenness reflected by NDVI was also reported by Gospodarek et al [33]. The authors explicitly demonstrated that NDVI value for A. pisum plants is correlated to amount of phosphorus fertiliser applied.…”
Section: Normalised Difference Vegetation Index (Ndvi)supporting
confidence: 68%
“…Easily available forms of phosphorus contained in the applied foliar fertiliser produced a positive effect on the nutritional status of maize in the experimental variants F1 and F3, which was confirmed by the values of NDVI. A relationship between phosphorus and leaf greenness reflected by NDVI was also reported by Gospodarek et al [33]. The authors explicitly demonstrated that NDVI value for A. pisum plants is correlated to amount of phosphorus fertiliser applied.…”
Section: Normalised Difference Vegetation Index (Ndvi)supporting
confidence: 68%
“…There are different opinions about the fertilization of peas. Some researchers say that pea fertilizer rates depend on nutrients in the soil [ 20 ]. Huang et al [ 17 ] found that when before sowing in soil and NO 3 -N was low (10 kg·ha −1 ), an application of starter N positively influenced pea yield (up to +19%); however, under higher initial soil NO 3 -N (44 kg·ha −1 ), the application of starter N reduced pea yield.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that in soil with a high nitrate–nitrogen content, starter N application had a detrimental effect on pea germination, and nodulation and seed yield [ 17 ]. The efficiency of fertilizers is governed by meteorological conditions and the nutrient content in the soil [ 18 , 19 ]; therefore, recommended NPK rates can vary widely [ 20 , 21 ]. The phosphorus and potassium requirements of peas vary depending on the growing conditions [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Index (NDVI) is one of the most widely used and reliable vegetation indices in monitoring vegetation change, emerging as a promising method to evaluate the green cover [39]. Google earth imagery is useful for the reliable validation of NDVI and semi-supervised image classification, which can save time and reduce cost [40].…”
Section: Introductionmentioning
confidence: 99%